Tempe sebagai Pangan Fungsional Antidiabetes - Nurwati Nurwati (JURNAL PANGAN, 2016)
Diabetes is one of the degenerative diseases that continue to increase from year to year and becomea global health problem. Diabetics need a food diet to maintain a normal blood glucose level. The adequatepattern of food consumption is a good solution for the diabetic people. Tempe is a food rich in bioactivecomponents that potentially to be antidiabetic through various mechanisms. The fermentation process ofsoybean to tempe can improve the health nutrition and reduce antinutrient substances that can be harmfulto health. The consumption of tempe as a part of good diet supported by good processing can be analternative therapy solution in the treatment of diabetes disease.